The impact of subscribing to directors’ and officers’ liability insurance on corporate financialization: Evidence from China - Peng, Cheng; Fu, Wenting; Zhang, Xinyu; Jiang, Hui (Frontiers in Psychology, 2022)
As an important corporate governance mechanism, directors’ and officers’ liability insurance is theoretically associated with corporate financialization because it directly affects incentive constraints and risk preference of enterprise managers. However, whether there is a causal relationship in fact has not been sufficiently empirically investigated. Using a sample of Chinese non-financial listed companies in Shanghai and Shenzhen A-shares from 2008 to 2020, this paper empirically analyzes how corporate subscription to directors’ and officers’ liability (D&O) insurance affects corporate financialization and examines the mediating role played by risk-taking, financing constraints, and audit quality. The study finds that corporate subscription to D&O insurance increases corporate financialization. In terms of the influential mechanism, subscription to D&O insurance promotes financialization by increasing risk-taking, alleviating financing constraints, and improving audit quality. In addition, the results in the heterogeneity analysis suggest that the promotion of financialization by subscribing to D&O insurance is more significant in state-owned enterprises, growth and decline stage enterprises, and non-dual-employment enterprises.